2023
DOI: 10.1186/s13049-023-01127-4
|View full text |Cite
|
Sign up to set email alerts
|

From tradition to innovation: a comparison of the traditional 4-step approach versus a blended learning modification for technical skills teaching

Elonka Bergmans,
Alistair Billington,
Karl-Christian Thies

Abstract: Background This experimental study was performed to evaluate the role of blended learning for technical skill teaching on the European Trauma Course (ETC). While online modules are extensively used for theoretical teaching, their role in skills training remains less well explored. The ETC currently relies on the established 4-step technique for teaching technical skills. However, the required large cohort of skilled instructors and the time intensity prove increasingly challenging in a current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“… 27 Transferring parts of trauma-related motor skill teaching to a virtual environment enhances efficiency and reduces the time required for face-to-face instruction. 28 Innovative methods such as serious gaming bridge the gap between theoretical knowledge and practical skills and provide immersive experiences in real-life trauma scenarios. 29 The emergence of virtual reality (VR) in medical education presents opportunities for team-based trauma training in risk-free environments.…”
Section: Evolution Of the Programme From 2008 To 2023mentioning
confidence: 99%
“… 27 Transferring parts of trauma-related motor skill teaching to a virtual environment enhances efficiency and reduces the time required for face-to-face instruction. 28 Innovative methods such as serious gaming bridge the gap between theoretical knowledge and practical skills and provide immersive experiences in real-life trauma scenarios. 29 The emergence of virtual reality (VR) in medical education presents opportunities for team-based trauma training in risk-free environments.…”
Section: Evolution Of the Programme From 2008 To 2023mentioning
confidence: 99%
“…The study found that integrated learning assistance, reflection, home hospital training and teaching, and multidisciplinary team training were insufficient. Bergmans et al (2023) investigated to determine if blended learning, which mixes conventional four-step instruction with pre-course online components, is equally effective and involves less time to complete. A randomized, multi-center research compared a 4-step face-to-face pelvic binder training method to a blended one.…”
Section: Literature Reviewmentioning
confidence: 99%
“… There has been rapid development in BL adoption focused on improving teaching and learning outcome. Prior studies assessed the effectiveness of BL by comparing the traditional teaching and online teaching [33,34,35].…”
Section: Innovative Pedagogical Approachesmentioning
confidence: 99%